Some embryology features of the Fumana procumbens (Dun.) Gren. et Godr. (fam. Cistaceae) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Investigation results of formation processes of the generative structures, features of the pollination, fertilization and embryogenesis of the Fumana procumbens have been presented.
Keywords: micro- and megasporogenesis, embryogenesis, Fumana procumbens.